Efficacy of miRNA-modified mesenchymal stem cell extracellular vesicles in spinal cord injury: A systematic review of the literature and network meta-analysis - Yang, Zhelun; Rao, Jian; Liang, Zeyan; Xu, Xiongjie; Lin, Fabin; Lin, Yike; Wang, Chunhua; Chen, Chunmei (Frontiers in Neuroscience, 2022)
Background: Although some previous studies have indicated that extracellular vesicles (EVs) secreted from miRNA-modified mesenchymal stem cells (MSCs) may be more effective as compared with control EVs in the treatment of rats with spinal cord injuries (SCI), the efficacy of this treatment modality remains controversial. Objectives: The current study comprehensively evaluated the efficacy of different administered doses of EVs, including miRNA-overexpressing MSCs-derived EVs, among SCI rats. The efficacy of EVs’ treatment was evaluated in different SCI models to provide evidence for preclinical trials. Methods: We extensively searched the following databases to identify relevant studies: PubMed, Embase, Scopus, The Cochrane Library, and Web of Science (from inception to July 20, 2022). Two trained investigators independently screened literature, extracted the data, and evaluated literature quality. Results: Thirteen studies were included in this network meta-analysis. The results demonstrated that miRNA-overexpressing MSCs-derived EVs (100 μg and 200 μg of total protein of EVs) significantly improved hind limb motor function in rats at early stages of SCI (i.e., at 3 days after injury) as compared with EVs (100 μg and 200 μg of total protein of EVs, respectively). However, in the middle and late stages (14 and 28 days), there were no statistically significant differences between EVs with 200 μg dosages and miRNA-loaded EVs with 100 μg dosages. In the late stages (28 days), there were no statistically significant differences between EVs with 100 μg dosages and miRNA-loaded EVs with 200 μg dosages. We found that miRNA-overexpressing MSCs-derived EVs significantly improved motor function among early-stage SCI rats in a compression and contusion model (3 days) as compared with MSCs-derived EVs and miRNA-overexpressing MSCs-derived EVs likewise significantly improved motor function among SCI rats in a contusion model at middle and late stages (14 and 28 days). Conclusion: Our results suggest that miRNA-overexpressing MSCs-derived EVs (200 μg of total protein of EVs) may be the best choice for the effective treatment of SCI, and miRNA-overexpressing MSCs-derived EVs may likewise be the best choice for treating contusions. However, there are some risks of bias in our included studies, and the mechanisms underlying the efficacy of EVs remain unclear.